Deciphering human ribonucleoprotein regulatory networks. Issue 2 (5th December 2018) - Mukherjee, Neelanjan; Wessels, Hans-Hermann; Lebedeva, Svetlana; Sajek, Marcin; Ghanbari, Mahsa; Garzia, Aitor; Munteanu, Alina; Yusuf, Dilmurat; Farazi, Thalia; Hoell, Jessica I; Akat, Kemal M; Akalin, Altuna; et al.
Abstract: RNA-binding proteins (RBPs) control and coordinate each stage in the life cycle of RNAs. Although in vivo binding sites of RBPs can now be determined genome-wide, most studies typically focused on individual RBPs. Here, we examined a large compendium of 114 high-quality transcriptome-wide in vivo RBP–RNA cross-linking interaction datasets generated by the same protocol in the same cell line and representing 64 distinct RBPs. Comparative analysis of categories of target RNA binding preference, sequence preference, and transcript region specificity was performed, and identified potential posttranscriptional regulatory modules, i.e. specific combinations of RBPs that bind to specific sets of RNAs and targeted regions. These regulatory modules represented functionally related proteins and exhibited distinct differences in RNA metabolism, expression variance, as well as subcellular localization. This integrative investigation of experimental RBP–RNA interaction evidence and RBP regulatory function in a human cell line will be a valuable resource for understanding the complexity of post-transcriptional regulation.